2008
DOI: 10.1097/hjh.0b013e3282f2450b
|View full text |Cite
|
Sign up to set email alerts
|

Combination of exercise and losartan enhances renoprotective and peripheral effects in spontaneously type 2 diabetes mellitus rats with nephropathy

Abstract: These results suggest that both exercise and losartan have renoprotective effects, and the combination of exercise and losartan provided greater renoprotective effects than losartan alone, and may affect macrophage infiltration, mesangial activation, and podocyte loss in this model of diabetic nephropathy. It is also suggested that exercise has a specific renoprotective effect that is not related to SBP reduction, and can enhance endurance without renal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 34 publications
5
43
2
Order By: Relevance
“…It should be noted, however, that losartan was adjusted weekly on the basis of body weight, so that the lower systolic blood pressure observed in the trained animals was not due to under-dosing losartan in the heavier, sedentary animals. These blood pressure data are similar to that reported by Tufescu et al (2008) who showed a 10-15 mmHg higher systolic blood pressure in losartan treatment alone versus exercise + losartan 6 weeks after the initiation of therapy. Thus while exercise together with losartan was more eVective in reducing blood pressure; absolute ventricular mass, length, and atrial mass were similar between trained and sedentary groups.…”
Section: Discussionsupporting
confidence: 92%
“…It should be noted, however, that losartan was adjusted weekly on the basis of body weight, so that the lower systolic blood pressure observed in the trained animals was not due to under-dosing losartan in the heavier, sedentary animals. These blood pressure data are similar to that reported by Tufescu et al (2008) who showed a 10-15 mmHg higher systolic blood pressure in losartan treatment alone versus exercise + losartan 6 weeks after the initiation of therapy. Thus while exercise together with losartan was more eVective in reducing blood pressure; absolute ventricular mass, length, and atrial mass were similar between trained and sedentary groups.…”
Section: Discussionsupporting
confidence: 92%
“…Rats were allowed to eat ad libitum, but we found no differences in body weight or food consumption as was found previously [31]. This could be due to shorter and less intense exercise schedule compared with other experimental studies [11][12][13][14], or intermittent training (ie, not performed during weekends). Thus, naturally hyperphagic OZR could replenish the energy expenditure.…”
Section: Discussioncontrasting
confidence: 53%
“…A substantial body of evidence showed the renoprotective effects of moderate exercise in type 1 and type 2 diabetes mellitus patients as well as in animal models of diabetic nephropathy [9][10][11][12][13][14]. However, the early events leading to renoprotection were not yet identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that these diff erences can be due to the variety in the duration and intensity of exercise (Virvidakis et al 1986;Poortmans et al 1996). Recent studies have demonstrated that chronic exercise has benefi cial eff ects that reduce the early progression of diabetic nephropathy (Tufescu et al 2008;Ito et al 2015). In recent years, research interest has been increased in the fi eld of aspects related to the body's response to exercise, in which miRNAs appear to play a key role.…”
mentioning
confidence: 99%